Effective practices in enhancing autonomous English language learning through YouTube - Ritueli Daeli; Santosa Santosa (Universitas Muhammadiyah Malang, 2025)
This study investigates the potential of YouTube as a tool for autonomous English language learning, focusing on its effectiveness, learner engagement strategies, and associated challenges. By analyzing data from in-depth interviews with ten intermediate-level English learners, the research explores the impact of diverse YouTube content, including instructional videos, vlogs, and conversational media, on language acquisition. Findings highlight the platform’s capacity to provide authentic language exposure, foster learner motivation, and cater to varying proficiency levels and interests. Strategies such as note-taking, pausing, and the use of subtitles enhance engagement and comprehension, while interactive features like comments promote active language practice. However, the study identifies significant challenges, including the overwhelming quantity and variable quality of available content, which may hinder learners’ ability to find reliable sources. The platform’s algorithm-driven design can also distract learners, reducing their focus and productivity. Additionally, the absence of structured guidance requires learners to exhibit high levels of self-discipline and motivation, often challenging for autonomous learners. Despite these limitations, YouTube emerges as a valuable supplementary tool, offering flexibility, accessibility, and a personalized learning experience that complements formal language instruction. The study underscores the need for curating high-quality educational content and developing tools to support self-regulation among learners. Future research should explore integrating YouTube with traditional pedagogical methods and leveraging its interactive features to enhance learner outcomes. This research contributes to understanding the role of digital platforms in language education, offering insights into optimizing their use for autonomous learning.